2021
DOI: 10.1111/bre.12525
|View full text |Cite
|
Sign up to set email alerts
|

Cambrian syn‐rift tectonic pulses at unconformity‐bounded carbonates in the Avalon Zone of Newfoundland, Canada

Abstract: In the Avalon Zone of SE Newfoundland, several Terreneuvian to Cambrian Series 2 carbonate bodies occur associated with paraconformities and onlapping geometries. Their stratigraphic discontinuities and related gaps represent syn-rift episodes characterized by sharply tilted and downfaulted blocks and deposition of chaotic megabreccia beds and conglomerates on neighbouring footwall areas. Microbial and shelly carbonate production nucleated on tectonically unstable palaeohorsts, where stromatolitic crusts and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 96 publications
1
9
0
Order By: Relevance
“…Interpretation of the carbonate production and the record of climatically sensitive indicators along the margins of the subtropical to temperate Cambrian rifts that fringed West Gondwana (and probably Baltica), prior to and during the Ordovician opening of the Rheic Ocean (Van Staal et al, 1998;Nance et al, 2012;Waldron et al, 2022), is essential to the improvement of existing palaeogeographical models. This paper, which complements a former report of sedimentological features from the same palaeogeographical area ( Alvaro, 2021), presents: (i) an analysis and review of the sedimentary and oceanographic factors that controlled the nucleation, growth and demise of the microbial-shelly carbonate factories developed in a Cambrian rift transect preserved in the Avalon Zone of southeast Newfoundland; (ii) an interpretation of the palaeoecological patterns and evolution within the transect, according to the redox conditions and phosphate availability; and (iii) a comparison of reefal and non-reefal frameworks with neighbouring rift-related and passive-margin settings in similar low to mid-latitudes.…”
Section: Introductionsupporting
confidence: 80%
See 2 more Smart Citations
“…Interpretation of the carbonate production and the record of climatically sensitive indicators along the margins of the subtropical to temperate Cambrian rifts that fringed West Gondwana (and probably Baltica), prior to and during the Ordovician opening of the Rheic Ocean (Van Staal et al, 1998;Nance et al, 2012;Waldron et al, 2022), is essential to the improvement of existing palaeogeographical models. This paper, which complements a former report of sedimentological features from the same palaeogeographical area ( Alvaro, 2021), presents: (i) an analysis and review of the sedimentary and oceanographic factors that controlled the nucleation, growth and demise of the microbial-shelly carbonate factories developed in a Cambrian rift transect preserved in the Avalon Zone of southeast Newfoundland; (ii) an interpretation of the palaeoecological patterns and evolution within the transect, according to the redox conditions and phosphate availability; and (iii) a comparison of reefal and non-reefal frameworks with neighbouring rift-related and passive-margin settings in similar low to mid-latitudes.…”
Section: Introductionsupporting
confidence: 80%
“…However, many questions remain, particularly regarding the interplay between coastal upwelling, microbial productivity, co-occurrence of various phosphate and Fe-redox indicators (i.e. chamosite, hematite and goethite), and potential links between reefal versus non-reefal structures from the Avalonian rift and other penecontemporaneous rift and passive-margin basins (see recent discussions in Alvaro, 2021;Alvaro et al, 2023). On other Cambrian rift basins fringing West Gondwana, different scales of tectonic deformation influenced the nucleation, growth and demise of carbonate factories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cover sequence deposition was controlled by terminal Edicaran–Ordovician syndepositional faulting along the Avalon transform fault (Atf) (Landing, 1996; Landing et al 2022; Landing et al 2023). Activity on the Atf produced NNE-striking faults (modern coordinates) and elongated NNE-striking basins and uplifts in a transtensional regime that was not a ‘rift environment’ ( contra Álvaro, 2021; Álvaro et al 2022). The SE migration of Avalonian depocenters through the Early Cambrian (Fig.…”
Section: Geological Settingmentioning
confidence: 99%
“…Their stratigraphy was summarized by Berry and Osberg (1989), based on compilations of earlier work (Neuman, 1967(Neuman, , 1984Hall, 1970). Van Staal et al, 2016, 2021 compared the Popelogan inlier with the inliers of northern Maine and showed that all have comparable stratigraphies.…”
Section: Northern Maine Inliersmentioning
confidence: 99%